Improved management of Panicum maximum cv. Likoni. Its effect on the productive and economic response of Siboney heifers (5/8 Holstein and 3/8 Cebu) - Fernández Mayer, A.; Zamora, A.; Mejías, R.; Torres, V.; Martín, P. C. (Cuban Journal of Agricultural Science, 2018)
Livestock production takes place in Cuba and in the rest of Latin America and the Caribbean, especially in adverse regions (climate and soil) to produce forage, displaced by agriculture. In tropical and subtropical regions, it is generally sought; higher forage production per hectare, regardless of its quality. Hence, the objectives of this study were to evaluate the production and quality of Panicum maximum cv. Likoni in different stages of maturity and determine management strategies that allow producing more meat at the lowest possible cost. For this, traditional management with respect to improved management was evaluated. Traditional management is the grazing of tropical forages, without eliminating the old grass from the previous season (dry season); on a plot for several days (moderate to low stocking rate); at the start of grazing from 1.0 to 1.2 m in height, with additional supplementation low or no. The improved management proposes to cut the old forage from the previous season (± 40-50 % dead) up to 20-25 cm in height, at 45- 60 d before the start of the new season, with a mower or with the animal's teeth, to facilitate a healthy and good quality regrowth from 0.40 to 1.0 m in height with cutting the remaining forage, if necessary, high stocking rate and low proportion of an additional protein concentrate or without it, with soybean expeller. The experiment was conducted at the Instituto de Ciencia Animal (ICA) from the Republic of Cuba, with heifers from Siboney breed. The production and quality of the forage, the production of individual meat per hectare and the production cost were evaluated. It is concluded that the results of the nutritional, productive and economic analyzes of the test were in favor of improved management with respect to the traditional one. It is recommended to deepen these lines of research, with the purpose of improving the obtained results. Key words: Panicum maximum vc. Likoni, quality, meat production,improved and traditional management